Deciphering the growth behaviour of Mycobacterium africanum. - Florian Gehre; Jacob Otu; Kathryn DeRiemer; Paola Florez de Sessions; Martin L Hibberd; Wim Mulders; Tumani Corrah; Bouke C de Jong; Martin Antonio (Public Library of Science (PLoS), 2013)
Human tuberculosis (TB) in West Africa is not only caused by M. tuberculosis but also by bacteria of the two lineages of M. africanum. For instance, in The Gambia, 40% of TB is due to infections with M. africanum West African 2. This bacterial lineage is associated with HIV infection, reduced ESAT-6 immunogenicity and slower progression to active disease. Although these characteristics suggest an attenuated phenotype of M. africanum, no underlying mechanism has been described. From the first descriptions of M. africanum in the literature in 1969, the time to a positive culture of M. africanum on solid medium was known to be longer than the time to a positive culture of M. tuberculosis. However, the delayed growth of M. africanum, which may correlate with the less virulent phenotype in the human host, has not previously been studied in detail.We compared the growth rates of M. tuberculosis and M. africanum isolates from The Gambia in two liquid culture systems. M. africanum grows significantly slower than M. tuberculosis, not only when grown directly from sputa, but also in growth experiments under defined laboratory conditions. We also sequenced four M. africanum isolates and compared their whole genomes with the published M. tuberculosis H37Rv genome. M. africanum strains have several non-synonymous SNPs or frameshift mutations in genes that were previously associated with growth-attenuation. M. africanum strains also have a higher mutation frequency in genes crucial for transport of sulphur, ions and lipids/fatty acids across the cell membrane into the bacterial cell. Surprisingly, 5 of 7 operons, recently described as essential for intracellular survival of H37Rv in the host macrophage, showed at least one non-synonymously mutated gene in M. africanum.The altered growth behaviour of M. africanum might indicate a different survival strategy within host cells.